Distribution of PBDEs, HBCDs and PCBs in the Brisbane River estuary sediment. Issue 1 (15th July 2017) - Anim, Alfred K.; Drage, Daniel S.; Goonetilleke, Ashantha; Mueller, Jochen F.; Ayoko, Godwin A.
Abstract: To date, very little or no data exist in literature for some brominated flame retardants (BFRs) and polychlorinated biphenyls in Queensland sediments. These pollutants were measured in the sediments along the Brisbane River estuary. The target compounds were regularly detected in measurable concentrations: PBDEs = 33.3–97.8% ( n = 45), PCBs = 94.1–100% ( n = 51) and HBCDs = 79–98% ( n = 48). Consistently, > 90% of the observed ∑8 PBDE concentration was attributed to BDE-209. Mean PBDE levels (ng/g dry wt.) were: 4.4 ± 3.2 (∑8 PBDE) and 4.4 ± 3.0 (BDE-209) across 22 sampling sites. The mean ∑7 PCB and ∑ HBCD were 5.4 ± 4.5 and 1.0 ± 1.5 ng/g dry wt. respectively. The 25% (α-HBCD), 8% (β-HBCD) and 67% (γ-HBCD) diastereoisomer contributions observed were consistent with values reported in the literature. Contaminant levels are fairly distributed along the River and were generally low compared to similar studies around the world. Graphical abstract: Highlights: Measurable PBDEs, PCBs and HBCDs were detected in Brisbane River estuary sediment. Results represent post 2011/2013 flood data and a baseline for HBCD. BDE-209 is the most dominant PBDE congener. Compared to similar studies, Brisbane River sediments are less contaminated.